Innovación tecnológica Kipa en procesos de teñido de algodón reactivo alineados con las ODS en la empresa, para la producción de prendas artesanales - Cachay Anardo, Adriana Edith (2025)
Reactive dye is one of the most widely used for textile fiber dyeing due to the colorfastness properties that fibers exhibit after the dyeing process, which results from a covalent reaction between the dye and the fibers. However, to achieve adequate colorfastness levels, hydrolyzed dye must be removed through extensive rinsing. Consequently, there is a high consumption of resources such as water, time, and energy. Given the importance of preserving natural resources, particularly water—an essential element in the dyeing process—it is crucial to identify periods when water consumption can be minimized. The most significant water waste occurs during the soaping and rinsing stages after dyeing; approximately 70% of the water used in the reactive dyeing process is consumed during these stages. This research paper aims to optimize cotton dyeing through a process known as “Kipa” to reduce resource consumption, particularly water, and minimize the use of toxic substances, such as sodium chloride and auxiliary chemicals. Additionally, temporal and thermal parameters, including pH and affinity, and the costs of the products will be examined to optimize the dyeing process.